(untitled) - Carus, Clayton D. (New York, 1944)
This book introduce resources inherent in Japan position and conformation, human resources, agriculture, animal industries, mining, transportation...
Keywords: Nguồn tài nguyên thiên nhiên,Natural resources; Nhật Bản,Japan